The Reform of the Pension System in Italy - Hamann, A. (IMF Working Papers; Working Paper ;, 1997)
Italy's pension system was reformed in August 1995. The new system has various desirable long-run properties and, overall, it represents an improvement over earlier systems. However, it fails to address two longstanding problems: extremely high contribution rates, and a lack of provisions for dealing with the substantial deterioration in demographic ratios expected over the next 30-40 years.